Application ofImproved K-Medians forVMMigration - Soni, Palash; Mudgal, Ankur (International Journal of Computer Sciences and Engineering, 2025)
Use of Data mining techniques for managing Virtual Machine migration has been used in the past. Many researchers have applied different data mining techniques for the same and has been proven to be encouraging. Specially in cloud environment where thousands of virtual machines are employed at a time. For this proactive evaluation methods has been used by many researchers In this paper, such methods have been studied and improved k-median technique has been proposed for such migration. The results obtained discussed are showing better accuracy and performance.